Development administration: Jamaican adaptations - Jones, Edwin (CARICOM Publishers KingstonJM, 1992)
Focuses on the administration of policies of the social democratic regime in Jamaica during the decade of the 1970s. Appraises the efforts of policy leaders to adapt new administrative technologies and policy frameworks in an essentially hostile environment. Concludes that the Michael-Manley led PNP regime skilfully identified and largely succeeded in managing the critical policy areas of economic growth; social equity; international transactions and public sector management.